TINGKATKAN KEMAMPUAN MEMBACA AL QUR’AN MELALUI STRATEGI MEMBACA KERAS - LESTARI LESTARI (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2022)
The background of this study is about the ability to read the Qur'an in class VII A students of SMP Negeri 3 Bulukerto in the 2022/2023 academic year in learning Islamic Religious Education and Characteristics of the elements of the Qur'an and Hadith which are still low so that improvements are needed to improve the ability to read the Qur'an. The purpose of this study is to describe the increase in the ability to read the Qur'an in students. This research is a Classroom Action Research (CAR). The subjects of this study were students of class VII A of SMP Negeri 3 Bulukerto with a total of 30 students. This CAR design consists of two cycles using the Kemmis and Targgart models which include planning, action, observation, and reflection. Data collection techniques using observation, documentation and tests. The data analysis used is descriptive quantitative. The results showed that there was an increase in the percentage of the ability to read the Qur'an in class VII A students of SMP Negeri 3 Bulukerto. This can be seen from the results of observations in the pre-cycle the number of students who are fluent in reading the Qur'an as many as 5 people with an average score of 17% of the ability to read the Qur'an and is included in the low criteria. In the first cycle the number of students who read the Qur'an fluently were 10 people with an average score of 33% of the ability to read the Qur'an and included in the medium criteria. then in the second cycle the number of students who are fluent in reading the Qur'an as many as 20 people with an average score of 67% of the ability to read the Qur'an and is included in the high criteria. It can be concluded that the strategy of reading aloud can improve the ability to read the Koran of class VII A students of SMP Negeri 3 Bulukerto for the 2022/2023 academic year. ABSTRAKLatar belakang penelitian ini mengenai kemampuan membaca Al-Qur’an pada peserta didik kelas VII A SMP Negeri 3 Bulukerto Tahun Pelajaran 2022/2023 pada pembelajaran Pendidikan Agama Islam dan Budi Pekerti elemen Al-Qur’an Hadis yang masih rendah sehingga diperlukan perbaikan untuk meningkatkan kemampuan membaca Al-Qur’an. Tujuan dari penelitian ini untuk mendeskripsikan peningkatan kemampuan membaca Al-Qur’an pada peserta didik. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK). Subjek penelitian ini adalah peserta didik kelas VII A SMP Negeri 3 Bulukerto dengan jumlah 30 peserta didik. Desain PTK ini terdiri dari dua siklus dengan menggunakan model Kemmis dan Targgart yang meliputi perencanaan, tindakan, observasi, dan refleksi. Teknik pengumpulan data menggunakan observasi, dokumentasi dan tes. Analisis data yang digunakan adalah deskriptif kuantitatif. Hasil penelitian menunjukkan terdapat peningkatan persentase kemampuan membaca Al-Qur’an pada peserta didik kelas VII A SMP Negeri 3 Bulukerto. Hal ini dapat dilihat dari hasil observasi pada pra siklus jumlah peserta didik yang lancar membaca Al-Qur’an sebanyak 5 orang dengan nilai rata-rata kemampuan membaca Al-Qur’an sebesar 17% dan termasuk dalam kriteria rendah. Pada siklus I jumlah peserta didik yang lancar membaca Al-Qur’an sebanyak 10 orang dengan nilai rata-rata kemampuan membaca Al-Qur’an sebesar 33% dan termasuk dalam kriteria sedang. kemudian pada siklus II jumlah peserta didik yang lancar membaca Al-Qur’an sebanyak 20 orang dengan nilai rata-rata kemampuan membaca Al-Qur’an sebesar 67% dan termasuk dalam kriteria tinggi. Dapat disimpulkan bahwa strategi membaca keras dapat meningkatkan kemampuan membaca Al-Quran peserta didik kelas VII A SMP Negeri 3 Bulukerto Tahun Pelajaran 2022/2023.